The Relationship between Perceived Computer Competence and the Employment Outcomes of Transition-aged Youths with Visual Impairments. (January 2013) - Zhou, Li; Smith, Derrick W.; Parker, Amy T.; Griffin-Shirley, Nora
Introduction: The study reported here explored the relationship between the self-perceived computer competence and employment outcomes of transition-aged youths with visual impairments. Methods: Data on 200 in-school youths and 190 out-of-school youths with a primary disability of visual impairment were retrieved from the database of the first three waves (2001–05) of the National Longitudinal Transition Study–2. The relationship between the youths' self-perceived computer competence and having paid jobs was examined using binomial logistic regression, with other variables (gender, severity of vision loss, and multiple disability status) held constant. Results: For both the in-school and out-of-school youths, those with a high self-perceived computer competence were significantly more likely to have paid jobs than were those with a low self-perceived computer competence when gender, severity of vision loss, and multiple disability status were held constant. Moreover, for the in-school youths, those with multiple disabilities were significantly less likely to have paid jobs than were those with only vision loss when the other variables were held constant. Discussion: The findings indicate the importance of computer competence for youths with visual impairments to achieve successful transitions. Implications for practitioners: Computer training should be a key component of the vocational preparation of transition-aged youths with visual impairments. In addition, special attention should be given to youths with multiple impairments to help them catch up in both computer use and employment.